Genetic control of frit fly resistance in spring barley cultivars - A. G. Semenova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Over the last decade, the harmfulness of frit flies (Oscinella frit L., and O. pusilla Meig.) on barley and other cereals has increased significantly, which is associated with global climate change and widespread violations of agricultural practices (for example, the wide use of surface tillage techniques). A supplement or alternative to agrotechnical and chemical measures to control the abundance of phytophages is the breeding of resistant cultivars. This control method is economical, environmentally friendly, and harmless for beneficial organisms. Successful breeding for this trait requires identification of barley genotypes resistant to frit flies, and studying the mechanisms of such resistance and patterns of its inheritance.Materials and methods. Using provocative conditions of infestation with O. frit, the genetic control of resistance to the phytophage was studied in the spring barley cultivars ‘Belogorsky’ (k-22089, Leningrad Province) and ‘Nordic’ (k-22342, USA), when crossed with the susceptible cultivar ‘Krinichny’ (k-27605, Belarus). During the tillering period, damage to the main stems of the parent forms, as well as F1 and F2 hybrids, was assessed.Results and conclusions. The expected and factual ratios of phenotypes were calculated, taking into account the percentage of damage to homozygotes as well as heterozygotes (F1) for resistance and susceptibility genes. Incompletely dominant monogenic inheritance of the frit fly resistance trait was observed in the two studied cultivars. Their genes showed different expressiveness: the gene in cv. ‘Belogorsky’ controlled 15.4% of the insect damage to the main stems, and the gene in cv. ‘Nordic’ controlled larval damage to 5.3% of the stems. The studied accessions can be recommended as donors for breeding for frit fly resistance.